(untitled) (Global Scientific Review, 2023)
Currently, there is an ongoing issue of granting the Exclusive Economic Zone (EEZ) oncession to Vietnam that has, which is also the area being negotiated regarded for concession in the Republic of Indonesia’s Fisheries Management Area (WPPNRI) 711. These areas include the waters of the Karimata Strait, the Natuna Sea, and the South Natuna Sea, one of Indonesia’s strategic fishing areas. The Indonesian government will experience a substantial cost with the loss of potential income from marine natural resources in the region forever, as well as the reduction of Indonesia’s sovereign territory, so it is necessary to confirm the delimitation of the Indonesian EEZ area. This research also discusses Indonesia as a participant in UNCLOS 1982 ( United Nations Convention on the Law of the Sea) since 1996. During this time, Vietnamese and Chinese fishermen can be suspected of not respecting Indonesia’s sovereign rights and violating the law as stipulated in UNCLOS 1982 Article 56 paragraph (1), Article 240, Article 244, and Article 246